Implementation K-Means Algorithm to Grouping Student's Ability in Literacy at SMP Santi Yasa Petak - Widyasprana, Ngakan Putu; Mahendra, Ida Bagus Made (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 12 No 2 (2023): JELIKU Volume 12 No 2, November 2023, 2023)
Literacy is the ability of Indonesian language competence on the basis of reading and writing. Literacy skills in Indonesia are quite lagging behind other nations in the world. To improve literacy skills, we use the SAC (All Smart Children) approach with TaRL (Teaching at Right Level) learning. This approach can be realized by using one of the clustering methods, namely the K-Means Algorithm. The grouping will use data from the implementation of the literacy program at SMP Santi Yasa Petak in the span of 3 months and the modeling using the Rapid Miner application. The results obtained divided students into 2 clusters, namely a cluster of students who were able to carry out a literacy program of 8 people and a cluster of students who had not been able to carry out a literacy program of 5 people.